Wirkung von Lehrerfortbildungen auf Überzeugungen von Lehrkräften zu lernförderlichem Assessment im Fach Mathematik (mathematica didactica, 2021)
Teachers’ beliefs about teaching and learning of mathematics are said to be crucial if thinking about supporting students’ learning at school. That’s why several empirical studies discuss the influence of teachers’ beliefs as a part of teachers’ competence on the quality of teaching mathematics within the last years. Nevertheless, it’s known little about how teachers’ beliefs about teaching and learning (mathematics) can be changed successfully. Therefore, within a teacher training study as part of the research-project Co2CA the effect of teacher trainings on teachers’ beliefs has been observed empirically. Over a period of overall 10 weeks N = 30 mathematics teachers took part in teacher trainings dealing with formative assessment if teaching mathematical modelling (experimental group A; EG A). Another N= 37 teachers participated in teacher trainings dealing with general didactical ideas concerning mathematical modelling and mathematical problem solving (experimental group B; EG B). Next to assessing teachers’ pedagogical content knowledge about central ideas of formative assessment (PCK-FA) teachers’ beliefs about formative and summative assessment have been asked for several times. Analyzing the influence of these teacher trainings on teachers’ pedagogical content knowledge and teachers’ beliefs it can be pointed out: While teachers out of EG A outperform their counterparts out of EG B within the PCK-FA-test at the end of the teacher trainings, teachers’ beliefs about assessment in classroom within EG A do not change within 10 weeks of teacher training. Furthermore, discussing teachers’ beliefs by comparing teachers out of EG A with teachers out of EG B, only little differences in teachers’ beliefs about assessment in classroom do exist.